2021
DOI: 10.1126/sciadv.abj5293
|View full text |Cite
|
Sign up to set email alerts
|

SEC23A rescues SEC23B-deficient congenital dyserythropoietic anemia type II

Abstract: The COPII component SEC23A overlaps functionally with its paralogous protein and rescues the SEC23B-deficient CDAII defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…Indeed, we demonstrated that overexpression of SEC23A in SEC23B-silenced cells completely rescued the observed phenotype by re-activating BMP/SMADs signaling pathway and HAMP transcription. This is in agreement with a recent study on an erythroid SEC23B-deficient cellular model (HUDEP-2), whose CDA II phenotype was rescued by increased expression of SEC23A [48]. These results are highly relevant to suggest novel therapeutic approach for CDA II.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, we demonstrated that overexpression of SEC23A in SEC23B-silenced cells completely rescued the observed phenotype by re-activating BMP/SMADs signaling pathway and HAMP transcription. This is in agreement with a recent study on an erythroid SEC23B-deficient cellular model (HUDEP-2), whose CDA II phenotype was rescued by increased expression of SEC23A [48]. These results are highly relevant to suggest novel therapeutic approach for CDA II.…”
Section: Discussionsupporting
confidence: 92%
“…A dose-response relationship between the level of increased SEC23A expression in SEC23B deleted HUDEP-2 cells and the degree of rescue of the erythroid differentiation defect was noted. Increased expression of SEC23A by as little as 30 and 5% in undifferentiated and differentiated HUDEP-2 cells, respectively, resulted in significant improvement of the erythroid defects resulting from SEC23B deficiency [51 ▪ ]. Taken together, these findings indicate that strategies aimed at increasing SEC23A level, even by moderate amounts, are expected to be of therapeutic value for CDA II.…”
Section: Congenital Dyserythropoietic Anemia Type IImentioning
confidence: 71%
“…To address the discrepant mouse and human phenotypes resulting from SEC23B deficiency, a large body of work was performed demonstrating that SEC23B functionally overlaps with its closely related paralogous protein SEC23A. The functional overlap between SEC23A and SEC23B was supported by several lines of evidence, including studies showing overlapping interactomes for SEC23A and SEC23B [56], complementation of the yeast sec23 by both murine and human SEC23 paralogs [56], and rescue of the perinatal mortality and pancreatic degeneration resulting from murine SEC23B deficiency by expressing Sec23a from the endogenous locus of Sec23b [51 ▪ ,56]. Examination of the expression levels of SEC23A and SEC23B in wildtype mouse and human bone marrow and pancreas tissues demonstrated a greater dependency for SEC23B in human bone marrow and mouse pancreas tissues [56–58], consistent with the SEC23B deficient phenotypes in these species.…”
Section: Congenital Dyserythropoietic Anemia Type IImentioning
confidence: 99%
See 2 more Smart Citations